Discovery of Fungus-Specific Targets and Inhibitors Using Chemical Phenotyping of Pathogenic Spore Germination - Sébastien C. Ortiz (American Society for Microbiology, 2021)
ABSTRACT There is a critical need for new antifungal drugs; however, the lack of available fungus-specific targets is a major hurdle in the development of antifungal therapeutics. Spore germination is a differentiation process absent in humans that could harbor uncharacterized fungus-specific targets. To capitalize on this possibility, we developed novel phenotypic assays to identify and characterize inhibitors of spore germination of the human fungal pathogen Cryptococcus. Using these assays, we carried out a high-throughput screen of ∼75,000 drug-like small molecules and identified and characterized 191 novel inhibitors of spore germination, many of which also inhibited yeast replication and demonstrated low cytotoxicity against mammalian cells. Using an automated, microscopy-based, quantitative germination assay (QGA), we discovered that germinating spore populations can exhibit unique phenotypes in response to chemical inhibitors. Through the characterization of these spore population dynamics in the presence of the newly identified inhibitors, we classified 6 distinct phenotypes based on differences in germination synchronicity, germination rates, and overall population behavior. Similar chemical phenotypes were induced by inhibitors that targeted the same cellular function or had shared substructures. Leveraging these features, we used QGAs to identify outliers among compounds that fell into similar structural groups and thus refined relevant structural moieties, facilitating target identification. This approach led to the identification of complex II of the electron transport chain as the putative target of a promising structural cluster of germination inhibitory compounds. These inhibitors showed high potency against Cryptococcus spore germination while maintaining low cytotoxicity against mammalian cells, making them prime candidates for development into novel antifungal therapeutics. IMPORTANCE Fungal pathogens cause 1.5 million deaths annually, and there is a critical need for new antifungal drugs. However, humans and fungi are very similar on a molecular level, and so many drugs that kill fungi also damage human cells, leading to extreme side effects, including death. The lack of fungus-specific targets is a major hurdle in the development of antifungal therapeutics. Spore germination is a process absent in humans that could harbor fungus-specific targets. To capitalize on this possibility, we developed new assays to identify and characterize inhibitors of spore germination of the human fungal pathogen Cryptococcus. Using these assays, we identified and characterized 191 novel inhibitors of spore germination. These inhibitors showed high potency against Cryptococcus spore germination while maintaining low cytotoxicity against mammalian cells, making them prime candidates for development into novel antifungal therapeutics.